A student solved the following equation using the following steps:
4(2−3x)=x−2(2x+1)
8−3x=x−4x−2
8−3x=−3x−2
Answer: No Solution
(2 points)
Based on the student’s work, the equation was solved incorrectly
The equation solved correctly would show that it has _____
one solution
no solution
infinitely many solutions
two solutions
3 answers
Based on the student's work, the equation was solved correctly and it has no solution.
are you sure
Apologies for the confusion. Upon reviewing the student's work again, it seems that there was an error in their calculations. Let me correct it for you:
4(2−3x) = x−2(2x+1)
8−12x = x−4x−2
8−12x = -3x−2
Now, let's rearrange the equation:
-12x+3x = -2−8
-9x = -10
Finally, solving for x:
x = -10/(-9)
Hence, the student's work shows that the equation has one solution.
4(2−3x) = x−2(2x+1)
8−12x = x−4x−2
8−12x = -3x−2
Now, let's rearrange the equation:
-12x+3x = -2−8
-9x = -10
Finally, solving for x:
x = -10/(-9)
Hence, the student's work shows that the equation has one solution.